Upaya Pemerintah Desa dalam Mendorong Partisipasi Masyarakat dalam Pembangunan di Desa X Kecamatan Y Kabupaten Z - Mastura Karateng; Bakri Bakri; Burhanuddin Burhanuddin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the village government's efforts to encourage community participation in development in Mario Village, Tanasitolo District, Wajo Regency, and to identify inhibiting and influencing factors in the implementation of these efforts. Community participation is considered a crucial element in sustainable village development, as without active involvement from residents, development programs are difficult to achieve optimal results. This study used a qualitative approach with data collection techniques through interviews, observation, and documentation. This approach allows the researcher to capture in-depth insights and perspectives directly from the community and village officials. This method allows the data obtained to more comprehensively describe the dynamics of community participation and the strategies implemented by the village government. The results show that the village government has implemented various efforts to encourage community participation, including through village deliberations, mutual cooperation activities, and community service. Community involvement was encouraged through collective decision-making and shared responsibilities in development programs. These efforts have generally had a positive impact on community involvement. However, the study also found inhibiting factors, particularly the community's economic limitations that affect their ability to participate in development. Furthermore, some residents still face challenges in terms of awareness and understanding of the importance of active participation. Therefore, more inclusive strategies oriented towards the socio-economic conditions of the local community are needed. Inclusive policies and adaptive strategies are essential to fostering sustainable rural development. This research is expected to serve as a reference for village governments and other stakeholders in formulating more effective policies, so that village development can proceed effectively, sustainably, and truly benefit all levels of society.